2022
DOI: 10.3390/horticulturae8121183
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in Essential Oil Composition of Immortelle Cultivated in Serbia

Abstract: Our previous research has proven that the immortelle (Helichrysum italicum) essential oil (EO) grown in Serbia possesses respectable biological potential and desirable composition of volatile compounds with the potential for a wide range of applications in the food, cosmetics, and pharmaceutical industries. Within this study, the impact of seasonal variations (temperature, precipitation, and insolation) during three successive years (2017, 2018, and 2019), on the volatile profile of γ-curcumene + ar-curcumene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Apart from these plants, there are reports that climate conditions influence essential oil quality in other plants from the Apiaceae family, such as Angelica glauca [86], Anethum graveolens [87], and Petroselinum crispum [88], as well as plants from Lamiaceae (lavandin, sage, peppermint, and wild mint) [45,46,48,89] and Asteraceae (immortelle, Mexican mint marigold, Yakut wormwood) [90][91][92]. Bearing in mind that climate change is inevitable, this issue should be given much more attention.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from these plants, there are reports that climate conditions influence essential oil quality in other plants from the Apiaceae family, such as Angelica glauca [86], Anethum graveolens [87], and Petroselinum crispum [88], as well as plants from Lamiaceae (lavandin, sage, peppermint, and wild mint) [45,46,48,89] and Asteraceae (immortelle, Mexican mint marigold, Yakut wormwood) [90][91][92]. Bearing in mind that climate change is inevitable, this issue should be given much more attention.…”
Section: Discussionmentioning
confidence: 99%
“…The main compounds in SEOs from Serbia were found to be cis-thujone, followed by camphor, trans-thujone and 1,8-cineole [43]. The main compounds in the essential oil of sage from Serbia were cis-thujone, followed by camphor, trans-thujone and 1,8-cineole [43].The age of leaves had a significant influence on the SEO composition [44]. In the EO isolated from young leaves, sesquiterpenoid constituents dominated (50.7-57.0%) while EO from development leaves increased the amount of monoterpenoids (55.4-88.4%) with camphor (1.9-32.7%), cis-thujone (6.7-28.5%), α-humulene (3.4-33.3%) and viridiflorol (2.9-12.4%) as main components [44].…”
Section: Essential Oil Compositionmentioning
confidence: 96%
“…According to the total amount of thujone in SEO Perry et al [42] grouped sage into three chemotypes (high, 39-44%; middle, 22-28%; low, 9%) and the ratio of α-and βthujone (α/β 10:1; 1.5:1; 1:10). The sage use in our study belongs to the chemotype with a high content of thujone ranging from 23.5% in shaded plants to 43.2% in wild plants. The ratio of cis to trans-thujone depends on the origin of the sage plant and the cultivation methods.…”
Section: Essential Oil Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted on various plant species have shown that the accumulation of specialised metabolites depends on various environmental factors, including temperature, light, and soil moisture [14]. In the higher plant studied so far, such as Thymus [15], Rosmarinus [16,17], Helichrysum [18], Mentha [19], and Eugenia patrisii [20], variability in quantity or composition of essential oil content related to the season or different environmental conditions has also been demonstrated. Similarly, seasonal changes in the composition of volatile organic compounds (VOCs) were observed in one of the species of the genus Calypogeia, that is, in the previously analysed Calypogeia azurea [21].…”
Section: Introductionmentioning
confidence: 99%